2019
DOI: 10.21203/rs.2.14708/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of pregnancy induced hypertension on adverse perinatal outcomes in Tigray regional state, Ethiopia: a prospective cohort study

Abstract: Background: The prevalence of pregnancy-induced hypertension in Ethiopia ranges from 2.2 to 18.3%. However, so far little is known about the adverse perinatal outcomes of pregnancy-induced hypertension in Tigray regional state, Ethiopia. Therefore, the objective of this study was to assess the effect of pregnancy-induced hypertension on adverse perinatal outcomes in Tigray Regional State, Ethiopia. Methods: a prospective cohort study was conducted on a total sample of 782 pregnant women attending antenatal car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…High blood pressure in pregnancy is associated with adverse pregnancy outcomes for both mother and infant. Similar to findings from Ethiopia, we found that approximately a third of women classified as hypertensive at 1st ANC visit delivered preterm and LBW infants [ 40 ].…”
Section: Discussionsupporting
confidence: 84%
“…High blood pressure in pregnancy is associated with adverse pregnancy outcomes for both mother and infant. Similar to findings from Ethiopia, we found that approximately a third of women classified as hypertensive at 1st ANC visit delivered preterm and LBW infants [ 40 ].…”
Section: Discussionsupporting
confidence: 84%
“…Based on our inclusion criteria, only 25 articles were included and considered for final analysis. From those included studies, eight articles were done in Amhara region [ 20 , 32 , 33 , 39 – 43 ], seven in SNNP [ 31 , 44 – 49 ], four articles in AA [ 50 – 53 ] and Oromo [ 25 , 54 – 56 ] for each and one article in Tigray [ 57 ] and Ethiopian Somalia region [ 58 ] for each. Concerning to publication, one study was un-published (grey literature) [ 40 ] whereas the remaining 24 articles were published from 2005 to 2020 in different journals [ 20 , 25 , 31 – 33 , 39 , 41 – 50 , 52 , 53 , 55 – 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning to publication, one study was un-published (grey literature) [ 40 ] whereas the remaining 24 articles were published from 2005 to 2020 in different journals [ 20 , 25 , 31 – 33 , 39 , 41 – 50 , 52 , 53 , 55 – 58 ]. Regarding to study design, 15 articles were employed cross sectional [ 20 , 25 , 31 , 39 , 41 – 43 , 47 – 51 , 53 – 56 ] while the five studies were done using cohort [ 33 , 45 , 50 , 57 , 58 ] and case control design [ 32 , 40 , 44 , 46 , 52 ] for each studies scored five and above out of settled criteria for each study design according to JBI critical appraisal were included for this systematic review and meta analysis (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possible pathways to explain the observed protective effect of ANC attendance on the adverse pregnancy outcomes assessed in this study. First, antenatal care provides an opportunity for the early detection and appropriate management of pregnancy-related complications such as anaemia, malaria, gestational diabetes, infections, hypertension which are known to cause preterm birth, stillbirth, low birth weight, and small-for-gestational-age (40)(41)(42). Through antenatal assessment, women with these risk factors are identi ed and advised on the signs of complications, birth preparedness, and offered distinct attention to prevent adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%